Preparation method and application of anti-static PTFE composite film

By blending powdered polytetrafluoroethylene resin, aviation kerosene, composite modified antistatic agent and nanographite, the problem of electrostatic adsorption of PTFE film in high dust concentration environments is solved, good antistatic and wear resistance is achieved, and safety and service life are improved.

CN119505310APending Publication Date: 2025-02-25JIANGXI GUCHUAN TAPE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411660535.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

PTFE film is prone to electrostatic adsorption in an environment with high dust concentration, resulting in adhesion, clustering, aesthetics and safety hazards, limiting its application.

Method used

Anti-static PTFE composite films were prepared by blending powdered polytetrafluoroethylene resin, aviation kerosene, composite modified antistatic agent and nanographite. Anti-static films with a thickness of 8-16 μm were prepared by pressing extrusion, stretching and heat setting treatment.

Benefits of technology

It achieves good anti-static effect of PTFE film, avoids electric shock caused by static electricity, adsorbsorbing dust, improves safety, and has excellent wear resistance, extends the service life of the material.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a preparation method and application of an anti-static PTFE composite film, and belongs to the technical field of high polymer materials. The antibacterial polar fleece fabric comprises the following components in parts by weight: 70-79 parts of powdery polytetrafluoroethylene resin, 20-30 parts of aviation kerosene, 0.3-3 parts of a composite modified antistatic agent and 1-5 parts of nano graphite, maleic anhydride and quaternary ammonium salt in the composite modified antistatic agent cooperate to enhance hydrophilicity and hygroscopicity and effectively eliminate static electricity, in addition, maleic anhydride reacts with the surface of a material to form a conductive layer, charge release is accelerated, static accumulation is reduced, maleic anhydride, a quaternary ammonium salt compound and modified graphite are copolymerized, the antistatic performance is excellent, a wear-resistant protective film can be formed, and the service life of the material is prolonged. The wear resistance of the material is further improved; the anti-static PTFE composite film prepared by the invention not only has an excellent anti-static effect, but also has good wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and specifically relates to a preparation method and application of an antistatic PTFE composite film. Background Art

[0002] Polytetrafluoroethylene film (PTFE film) is widely used in clothing, transportation, electronics and electrical, and defense industries due to its excellent chemical stability, high and low temperature resistance, and non-stick properties.

[0003] However, in an environment with high dust concentration, PTFE membrane, as a good electrical insulating material, is easily adsorbed on the machine during plastic film processing due to static electricity and is difficult to detach. At the same time, static electricity causes the film to be easily adsorbed into clumps and difficult to unfold, seriously affecting product quality and service life, and limiting its application. Static electricity accumulation will not only cause the plastic to absorb dust in the air, affecting its appearance and reducing the value of the product, but will also cause adhesion problems during the plastic manufacturing process. In addition, the accumulation of static electricity may cause safety hazards such as electric shock, equipment failure and fire, and even cause explosion risks due to frictional static electricity, hindering the industrial furnace from achieving ultra-low emissions and increasing corporate costs and environmental risks. Therefore, the research and development of PTFE composite membranes with excellent anti-static properties has important practical significance and application value. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a method for preparing an antistatic PTFE composite membrane and application thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] An antistatic PTFE composite film comprises the following raw materials in parts by weight: 70-79 parts of powdered polytetrafluoroethylene resin, 20-30 parts of aviation kerosene, 0.3-3 parts of composite modified antistatic agent and 1-5 parts of nano graphite.

[0007] The composite modified antistatic agent is prepared by the following method:

[0008] Step A1: p-Chloromethylstyrene, trimethylamine and 2,6-di-tert-butyl-4-methylphenol are mixed, heated to 70°C for reaction under a nitrogen environment, heated and stirred for 3 minutes, and then reacted for 24 hours. After the system is cooled to 40°C, washed, filtered, and vacuum dried at 40°C to obtain a quaternary ammonium salt compound;

[0009] Further, the mass ratio of p-chloromethylstyrene, trimethylamine, and 2,6-di-tert-butyl-4-methylphenol is 28.18-29.12 g: 58.15-61.51 g: 0.36-0.40 g;

[0010] Step A2: carbon black, deionized water and anhydrous ethanol are mixed and stirred, heated in a water bath to 60° C., 3-trimethoxysilane acrylate is added dropwise, reacted for 1 hour, ultrasonically vibrated for 2 hours, filtered, washed, and vacuum dried for 3 hours to obtain modified carbon black;

[0011] Further, the usage ratio of carbon black, deionized water, anhydrous ethanol, and 3-trimethoxysilane propyl acrylate is 10-15 g: 230 g: 10-20 mL: 3-10 g;

[0012] Step A3: maleic anhydride and isoamyl acetate are mixed and reacted for 3 hours. Under nitrogen protection, azobisisobutyronitrile, toluene, quaternary ammonium salt compound and modified carbon black are added and stirred evenly. The mixture is reacted at 70° C. for 6 hours, centrifuged, filtered, washed, and vacuum dried at 45° C. to obtain a composite modified antistatic agent.

[0013] Furthermore, the usage ratio of maleic anhydride, isoamyl acetate, azobisisobutyronitrile, toluene, quaternary ammonium salt compound and modified carbon black is 0.2-0.4 mol: 1.16-2.14 g: 0.21-0.36 g: 90 mL: 1.06-3.12 g: 15-20 g.

[0014] A method for preparing an antistatic PTFE composite membrane specifically comprises the following steps:

[0015] S1: mixing powdered polytetrafluoroethylene resin, aviation kerosene, composite antistatic agent and nano-graphite to prepare a paste mixture;

[0016] S2: pushing and extruding the paste mixture, calendering, the calendering temperature is 30-60° C., and then heating to 300-340° C. to obtain a polytetrafluoroethylene membrane with a thickness of 80-120 μm;

[0017] S3: The polytetrafluoroethylene film is stretched transversely and longitudinally at the same time, with a transverse stretching ratio of 10-30 times and a longitudinal stretching ratio of 3-14 times, and then heat-set at a temperature of 300-340°C for 10-20 minutes, cut and rolled to obtain an antistatic PTFE composite film with a thickness of 8-16 μm.

[0018] The present invention also provides an application of the antistatic PTFE composite membrane prepared by the preparation method in a polytetrafluoroethylene coated filter material, wherein the polytetrafluoroethylene coated filter material comprises a clean air surface made by blending polyphenylene sulfide fibers and polytetrafluoroethylene fibers in a mass ratio of (1-4):1, a base fabric layer formed by interweaving polytetrafluoroethylene yarns in warp and weft, a dust-facing surface made by blending polyphenylene sulfide fibers and polytetrafluoroethylene fibers in a mass ratio of (1-4):1, and a coating layer made of the antistatic PTFE composite membrane, wherein the coating layer can filter the main components of dust and release static electricity in working conditions;

[0019] The base fabric layer is fixedly connected to the clean air surface, the dust facing surface is fixedly connected to the base fabric layer, and the coating layer is coated on the dust facing surface by hot melt coating, the temperature is 260-270°C, the pressure between the front and rear rubber rollers and the hot rollers is 0.2-0.7MPa, the spacing is 0.1-0.6mm, and the speed is 6-10m / min.

[0020] Beneficial effects of the present invention:

[0021] The antistatic PTFE composite film of the invention has good antistatic effect, avoids electric shock caused by static electricity, absorbs dust, improves safety, and also has excellent wear resistance, extending the service life of the material.

[0022] The composite modified antistatic agent prepared by the present invention has the advantage of being a macromolecular polymer and exhibits antistatic performance that surpasses that of traditional small molecule antistatic agents. The composite modified antistatic agent, under the action of 2,6-di-tert-butyl-4-methylphenol, utilizes the chlorine atom of p-chloromethylstyrene and the amino group of trimethylamine to undergo quaternization reaction to generate a positively charged quaternary ammonium salt compound, which not only enhances hydrophilicity and hygroscopicity, but also effectively eliminates static electricity of plastics due to the static elimination characteristics and strong adsorption of the quaternary ammonium salt; 3-trimethoxysilane acrylate is then hydrolyzed into silanol and graphite doped to generate modified graphite; finally, maleic anhydride and isoamyl acetate are mixed, and the initiator azobisisobutyronitrile is used to copolymerize the carbon-carbon double bonds of the quaternary ammonium salt compound, maleic anhydride and the carbon-carbon double bonds of the modified graphite to synthesize the composite modified antistatic agent. At high temperature, the anhydride groups of maleic anhydride in the composite modified antistatic agent react with the active groups on the material surface to form a conductive layer, which significantly improves the conductivity of the material surface, quickly releases the charge from the plastic surface, and effectively reduces static electricity accumulation. At the same time, maleic anhydride and quaternary ammonium salts work synergistically to enhance the hydrophilicity of the material surface and promote moisture absorption. After moisture absorption, the ions in the water film act as a conductive medium to accelerate the transfer and dissipation of charges, further enhancing the conductivity efficiency of surface ions, thereby effectively avoiding the negative impact of static electricity on production and product quality. In addition, maleic anhydride, quaternary ammonium salt compounds and modified graphite copolymers not only have excellent antistatic effects, but also can form a tough protective film during friction, with good wear resistance, further improving the wear resistance of the material. DETAILED DESCRIPTION

[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Embodiment 1: A method for preparing an antistatic PTFE composite membrane, comprising the following steps:

[0025] S1: weighing raw materials by weight, 70 parts of powdered polytetrafluoroethylene resin, 20 parts of aviation kerosene, 0.3 parts of composite modified antistatic agent (prepared in this embodiment), and 1 part of nanographite; blending powdered polytetrafluoroethylene resin, aviation kerosene, composite antistatic agent and nanographite to obtain a paste mixture;

[0026] S2: the paste mixture is pushed and extruded, calendered, the calendering temperature is 30°C, and then heated to 300°C to obtain a polytetrafluoroethylene membrane with a thickness of 80 μm;

[0027] S3: The polytetrafluoroethylene film is stretched transversely and longitudinally at the same time, the transverse stretching ratio is 10 times, and the longitudinal stretching ratio is 3 times, and then heat-setting treatment is performed at a temperature of 300° C. for 10 min, and then cut and rolled to obtain an antistatic PTFE composite film with a thickness of 8 μm;

[0028] The composite modified antistatic agent is prepared by the following method:

[0029] Step A1: 28.18 g of p-chloromethylstyrene, 58.15 g of trimethylamine and 0.36 g of 2,6-di-tert-butyl-4-methylphenol were mixed, and the temperature was raised to 70° C. for reaction under a nitrogen environment. After heating and stirring for 3 min, the reaction was continued for 24 h. After the system was cooled to 40° C., it was washed, filtered, and vacuum dried at 40° C. to obtain a quaternary ammonium salt compound;

[0030] Step A2: 10 g of carbon black, 230 g of deionized water and 10 mL of anhydrous ethanol were mixed and stirred, heated in a water bath to 60° C., and then 3 g of 3-trimethoxysilane propyl acrylate was added dropwise, reacted for 1 h, ultrasonically vibrated for 2 h, filtered, washed, and vacuum dried for 3 h to obtain modified carbon black;

[0031] Step A3: 0.2 mol maleic anhydride and 1.16 g isoamyl acetate were mixed and reacted for 3 h. Under nitrogen protection, 0.21 g azobisisobutyronitrile, 90 mL toluene, 1.06 g quaternary ammonium salt compound and 15 g modified carbon black were added and stirred evenly. The mixture was reacted at 70 ° C for 6 h, centrifuged, filtered, washed, and dried in vacuo at 45 ° C to obtain a composite modified antistatic agent.

[0032] Embodiment 2: A method for preparing an antistatic PTFE composite membrane, comprising the following steps:

[0033] S1: weighing raw materials by weight, 74 parts of powdered polytetrafluoroethylene resin, 25 parts of aviation kerosene, 1.6 parts of composite modified antistatic agent (prepared in this embodiment), and 3 parts of nano-graphite; blending the powdered polytetrafluoroethylene resin, aviation kerosene, composite antistatic agent and nano-graphite to obtain a paste mixture;

[0034] S2: the paste mixture is pushed and extruded, calendered, the calendering temperature is 45°C, and then heated to 320°C to obtain a polytetrafluoroethylene membrane with a thickness of 100 μm;

[0035] S3: The polytetrafluoroethylene film is stretched transversely and longitudinally at the same time, the transverse stretching ratio is 20 times, and the longitudinal stretching ratio is 8 times, and then heat-setting treatment is performed at a temperature of 320° C. for 15i n, and then cut and rolled to obtain an antistatic PTFE composite film with a thickness of 12 μm;

[0036] The composite modified antistatic agent is prepared by the following method:

[0037] Step A1: 28.66 g of p-chloromethylstyrene, 59.83 g of trimethylamine and 0.38 g of 2,6-di-tert-butyl-4-methylphenol were mixed, and the temperature was raised to 70° C. for reaction under a nitrogen environment. After heating and stirring for 3 min, the reaction was continued for 24 h. After the system was cooled to 40° C., it was washed, filtered, and vacuum dried at 40° C. to obtain a quaternary ammonium salt compound;

[0038] Step A2: 12 g of carbon black, 230 g of deionized water and 15 mL of anhydrous ethanol were mixed and stirred, heated in a water bath to 60° C., and then 6.5 g of 3-trimethoxysilane propyl acrylate was added dropwise, reacted for 1 h, ultrasonically vibrated for 2 h, filtered, washed, and vacuum dried for 3 h to obtain modified carbon black;

[0039] Step A3: 0.3 mol maleic anhydride and 1.65 g isoamyl acetate were mixed and reacted for 3 h. Under nitrogen protection, 0.28 g azobisisobutyronitrile, 90 mL toluene, 2.09 g quaternary ammonium salt compound and 17 g modified carbon black were added and stirred evenly. The mixture was reacted at 70 ° C for 6 h, centrifuged, filtered, washed, and dried in vacuo at 45 ° C to obtain a composite modified antistatic agent.

[0040] Embodiment 3: A method for preparing an antistatic PTFE composite membrane, comprising the following steps:

[0041] S1: weighing raw materials by weight, 79 parts of powdered polytetrafluoroethylene resin, 30 parts of aviation kerosene, 3 parts of composite modified antistatic agent (prepared in this embodiment), and 5 parts of nano-graphite; blending powdered polytetrafluoroethylene resin, aviation kerosene, composite antistatic agent and nano-graphite to prepare a paste mixture;

[0042] S2: The paste-like mixture is pushed and extruded, and calendered at a calendering temperature of 60° C., and then heated to 340° C. to obtain a polytetrafluoroethylene membrane with a thickness of 120 μm;

[0043] S3: The polytetrafluoroethylene film is stretched transversely and longitudinally at the same time, the transverse stretching ratio is 30 times, and the longitudinal stretching ratio is 14 times, and then heat-setting treatment is performed at a temperature of 340° C. for 20 min, and then cut and rolled to obtain an antistatic PTFE composite film with a thickness of 16 μm;

[0044] The composite modified antistatic agent is prepared by the following method:

[0045] Step A1: 29.12 g of p-chloromethylstyrene, 61.51 g of trimethylamine and 0.40 g of 2,6-di-tert-butyl-4-methylphenol were mixed, and the temperature was raised to 70° C. for reaction under a nitrogen environment. After heating and stirring for 3 min, the reaction was continued for 24 h. After the system was cooled to 40° C., it was washed, filtered, and vacuum dried at 40° C. to obtain a quaternary ammonium salt compound;

[0046] Step A2: 15 g of carbon black, 230 g of deionized water and 20 mL of anhydrous ethanol were mixed and stirred, heated in a water bath to 60° C., 10 g of 3-trimethoxysilane propyl acrylate was added dropwise, reacted for 1 h, ultrasonically vibrated for 2 h, filtered, washed, and vacuum dried for 3 h to obtain modified carbon black;

[0047] Step A3: 0.4 mol maleic anhydride and 2.14 g isoamyl acetate were mixed and reacted for 3 h. Under nitrogen protection, 0.36 g azobisisobutyronitrile, 90 mL toluene, 3.12 g quaternary ammonium salt compound and 20 g modified carbon black were added and stirred evenly. The mixture was reacted at 70 ° C for 6 h, centrifuged, filtered, washed, and dried in vacuo at 45 ° C to obtain a composite modified antistatic agent.

[0048] Comparative Example

[0049] This comparative example is an antistatic PTFE composite membrane, which differs from Example 3 in that an equal amount of ethoxylated stearyl phthalamide is used to replace the composite modified antistatic agent prepared in Example 3, and the rest are the same.

[0050] Performance test: The antistatic PTFE composite films prepared in Examples 1-3 and Comparative Examples 1-2 were cut into standard test sizes, and the surface resistivity test was performed according to GB / T1410-2006, and the friction and wear test was performed using GB3960-83 (the smaller the value of the wear index, the better the wear resistance); the test results are shown in the following table:

[0051] Example 1 Example 2 Example 3 Comparative Example Surface resistivity / Ω <![CDATA[8.6×10 15 ]]> <![CDATA[9.1×10 15 ]]> <![CDATA[7.9×10 15 ]]> <![CDATA[5.6×10 16 ]]> Wear index 63 59 62 79

[0052] It can be seen from the test data in the table that the antistatic PTFE composite film prepared in Example 1 has an excellent antistatic effect. It can also be seen from the above table that the antistatic PTFE composite film prepared in the present invention has good wear resistance.

[0053] The above contents are merely examples and explanations of the concept of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing an antistatic PTFE composite membrane, characterized in that: The following steps are involved: S1: weighing raw materials by weight, 70-79 parts of powdered polytetrafluoroethylene resin, 20-30 parts of aviation kerosene, 0.3-3 parts of composite modified antistatic agent, and 1-5 parts of nanographite; blending the powdered polytetrafluoroethylene resin, aviation kerosene, composite antistatic agent and nanographite to obtain a paste mixture; S2: pushing and extruding the paste mixture, calendering, the calendering temperature is 30-60° C., and then heating to 300-340° C. to obtain a polytetrafluoroethylene membrane with a thickness of 80-120 μm; S3: The polytetrafluoroethylene film is stretched transversely and longitudinally at the same time, with a transverse stretching ratio of 10-30 times and a longitudinal stretching ratio of 3-14 times, and then heat-set at a temperature of 300-340°C for 10-20 minutes, cut and rolled to obtain an antistatic PTFE composite film with a thickness of 8-16 μm.

2. The method for preparing an antistatic PTFE composite membrane according to claim 1, characterized in that: The composite modified antistatic agent is prepared by the following method: Step A1: p-Chloromethylstyrene, trimethylamine and 2,6-di-tert-butyl-4-methylphenol are mixed, heated to 70°C for reaction under a nitrogen environment, heated and stirred for 3 minutes, and then reacted for 24 hours. After the system is cooled to 40°C, washed, filtered, and vacuum dried at 40°C to obtain a quaternary ammonium salt compound; Step A2: carbon black, deionized water and anhydrous ethanol are mixed and stirred, heated in a water bath to 60° C., 3-trimethoxysilane acrylate is added dropwise, reacted for 1 hour, ultrasonically vibrated for 2 hours, filtered, washed, and vacuum dried for 3 hours to obtain modified carbon black; Step A3: maleic anhydride and isoamyl acetate are mixed and reacted for 3 hours. Under nitrogen protection, azobisisobutyronitrile, toluene, quaternary ammonium salt compound and modified carbon black are added and stirred evenly. The mixture is reacted at 70°C for 6 hours, centrifuged, filtered, washed, and dried in vacuo at 45°C to obtain a composite modified antistatic agent.

3. The method for preparing an antistatic PTFE composite membrane according to claim 2, characterized in that: The mass ratio of p-chloromethylstyrene, trimethylamine and 2,6-di-tert-butyl-4-methylphenol in step A1 is 28.18-29.12 g: 58.15-61.51 g: 0.36-0.40 g.

4. The method for preparing an antistatic PTFE composite membrane according to claim 2, characterized in that: In step A2, the usage ratio of carbon black, deionized water, anhydrous ethanol and 3-trimethoxysilane acrylate is 10-15g:230g:10-20mL:3-10g.

5. The method for preparing an antistatic PTFE composite membrane according to claim 2, characterized in that: In step A3, the usage ratio of maleic anhydride, isoamyl acetate, azobisisobutyronitrile, toluene and quaternary ammonium salt compound is 0.2-0.4 mol: 1.16-2.14 g: 0.21-0.36 g: 90 mL: 1.06-3.12 g.

6. An application of an antistatic PTFE composite membrane prepared by the preparation method according to any one of claims 1 to 5 in a polytetrafluoroethylene coated filter material, characterized in that: The polytetrafluoroethylene coated filter material comprises a clean air surface made by blending polyphenylene sulfide fiber and polytetrafluoroethylene fiber in a mass ratio of (1-4):1, a base fabric layer formed by interweaving polytetrafluoroethylene yarns in warp and weft, a dust-facing surface made by blending polyphenylene sulfide fiber and polytetrafluoroethylene fiber in a mass ratio of (1-4):1, and a coating layer made of the antistatic PTFE composite film; The base fabric layer is fixedly connected to the clean air surface, the dust facing surface is fixedly connected to the base fabric layer, and the coating layer is coated on the dust facing surface by hot-melt coating.

7. The use according to claim 6, characterized in that: The process parameters of hot-melt coating of the coating layer on the dust-facing surface are: temperature 260-270°C, pressure between the front and rear rubber rollers and the hot rollers 0.2-0.7MPa, spacing 0.1-0.6mm, and speed 6-10m / min.